(untitled) (TECHNICAL SCIENCE RESEARCH IN UZBEKISTAN, 2025)
Neuroeducation is an interdisciplinary field combining neuroscience, psychology, and pedagogy to better understand how students learn and how educators can adapt their methods to align with brain function. This paper investigates the neural mechanisms underlying learning and memory, focusing on brain plasticity, attention, emotional regulation, and sleep.